Believarexic - Johnson, J. J., 1973- (2015)
An autobiographical novel in which fifteen-year-old Jennifer Johnson convinces her parents to commit her to the Eating Disorders Unit of an upstate New York psychiatric hospital in 1988, where the treatment for her bulimia and anorexia is not what she expects.
Keywords: Psychiatric hospitals -- Juvenile fiction; Anorexia nervosa -- Juvenile fiction; Bulimia -- Juvenile fiction; Depression, Mental -- Juvenile fiction; Dysfunctional families -- Juvenile fiction; Novels in verse; New York (State) -- History -- 20th century -- Juvenile fiction; Fiction; History; Juvenile works